Numerical Analysis of Reinforced Concrete Piles under Blast Loads - Bhagya Jayasinghe; Anthony T.C. Goh; Zhiye Zhao; Hongyuan Zhou; Yilin Gui (Institut Teknologi Sepuluh Nopember, 2017)
Pile foundations are commonly used as foundation systems for high-rise buildings and bridges. This paper uses a fully coupled three dimensional numerical modelling procedure to study the performance of pile foundations subjected to ground shocks induced by surface explosions. The comprehensive numerical model includes the pile, surrounding soil, air and the explosive. Appropriate material models are incorporated and dynamic non-linear analysis is carried out using finite element techniques. The soil in which the pile is buried could influence the blast performance of the pile. A parametric study is hence carried out to evaluate the effects of soil properties of density, friction angle, cohesion and Poisson’s ratio on the blast performance of the pile. It is found that density and cohesion of soil have significant effects on the deflection of the pile under blast loading. Poisson’s ratio has some effect, but effect of the soil friction angle is not very significant. The findings of this study will serve as a benchmark reference for future analysis and design of pile foundations to blast loading.